2013
DOI: 10.1016/j.neuroimage.2012.09.077
|View full text |Cite
|
Sign up to set email alerts
|

The NTSR1 gene modulates the association between hippocampal structure and working memory performance

Abstract: The genetic and neural basis of working memory (WM) has been extensively studied. Many dopamine (DA) related genes, including the NTSR1 gene (a DA modulator gene), have been reported to be associated with WM performance. The NTSR1 protein is predominantly expressed in the cerebral cortex and the hippocampus, the latter of which is closely involved in WM processing based on both lesion and fMRI studies. Thus far, however, no study has examined the joint effects of NTSR1 gene polymorphism and hippocampal morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 78 publications
1
7
0
Order By: Relevance
“…These results indicate that WM gradually develops with age, consistent with the findings from previous studies [3]. Because episodic memory is dependent on the hippocampus [36] and the existence of a dopamine-related gene associated with WM (NTSR1 gene) it is thought that the hippocampus is related to WM [37]. Based on these results which showed that 12-year-olds had higher accuracy rates than all the other groups in one-card-learning, and the fact that previous research has shown that WM increases until adolescence, we deduced that episodic memory and WM increase in accordance with the maturation of the hippocampus.…”
Section: Discussionsupporting
confidence: 90%
“…These results indicate that WM gradually develops with age, consistent with the findings from previous studies [3]. Because episodic memory is dependent on the hippocampus [36] and the existence of a dopamine-related gene associated with WM (NTSR1 gene) it is thought that the hippocampus is related to WM [37]. Based on these results which showed that 12-year-olds had higher accuracy rates than all the other groups in one-card-learning, and the fact that previous research has shown that WM increases until adolescence, we deduced that episodic memory and WM increase in accordance with the maturation of the hippocampus.…”
Section: Discussionsupporting
confidence: 90%
“…ErbB3 is a member of the epidermal growth factor receptor family of receptor tyrosine kinases and is involved in neural crest differentiation and the development of the sympathetic nervous system and neural crest derivatives such as Schwann cells [45]. The Ntsr1 receptor belongs to the large superfamily of G-protein-coupled receptors and is reported to modulate the association between hippocampal structure and working memory performance [46]. Itpr1 is a calcium channel which is responsible for Ca 2+ mobilization from intracellular sores in the endoplasmic reticulum [47].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive and behavioral measures included working memory, executive functions (assessed with the Attention Network Test, the Wisconsin Card Sorting Task, and a reversal learning test), IQ, personality and motivation traits (for example, intrinsic and extrinsic motivation) and so on. Detailed information on cognitive and behavioral data acquisition, genotyping and statistical analysis can be found in the previous studies 47,48 and Supplementary Data and Supplementary Table S1.…”
Section: Cognitive Function Studiesmentioning
confidence: 99%